Recognition of Movement Disorders as Cardinal Features of Anti-IgLON5 Disease: Expanding the Clinical Spectrum. (5th October 2021) - Atadzhanov, Masharip; Chishimba, Lorraine
Abstract : Movement disorders are a prominent and common feature in many autoantibody-mediated neurologic diseases. 1 Anti-IgLON5 disease is a recently discovered antibody-mediated neurodegenerative disorder with antibodies against extracellular epitopes for IgLON5, a neuronal cell adhesion protein of unknown function. 2 The disorder shows a remarkable association with the HLA-DQB1*0501 and HLA-DRB1*1001 alleles, and postmortem studies demonstrate a novel neuronal tauopathy involving predominantly the hypothalamus and tegmentum of the brainstem. The core symptoms that led to its discovery were the distinct sleep-related breathing disorders characterized by REM and non-REM parasomnias. 2 Initial descriptions of the syndrome suggested that 4 symptoms made up the phenotype of this disorder: sleep disorders, a bulbar syndrome, progressive supranuclear palsy, and cognitive decline with or without chorea. 3 However, the spectrum of this disease continues to expand. One subsequent case study reported a motor neuron disease-like phenotype, and another reported peripheral involvement. 4, 5 Regardless of phenotype, anti-IgLON5 disease has an insidious onset and protracted clinical course spanning months to years. With an estimated incidence of 1 in 150, 000 people, it affects people between 45 and 75 years of age. 6 Only 10% of patients have a history of autoimmune disease, 7 and the disorder is not clearly paraneoplastic, with a history of malignancy present in only 11% of individuals.